ONE IS NOT BORN AN AFRICAN WOMAN: BODY, EXISTENCE, AND BECOMING IN A PHENOMENOLOGY OF THE FEMININE - Nery Carneiro, Everton; Libertadoira Borges Carneiro, Ivana (Revista Gênero e Interdisciplinaridade, 2026)
This article examines African female existence, understood from the perspective of the lived body and the historical conditions that permeate gender, power, and subjectivity. Its objective is to critically analyze the biological, culturalist, and patriarchal determinisms present in studies on African women, proposing a phenomenological reading of female experience as an open and situated process. The methodology adopted is qualitative, of a theoretical-interpretative nature, grounded in existential phenomenology and critical discourse analysis. The theoretical framework articulates Simone de Beauvoir, Merleau-Ponty, Bibi Bakare-Yusuf, and Frantz Fanon, in dialogue with contemporary African feminist studies. As a result, the article shows that African women cannot be thought of as a homogeneous essence or cultural destiny, but as embodied subjectivity, marked by plurality and historical becoming, highlighting existential phenomenology as a fertile ethical-political horizon for gender studies in Africa.